2007
DOI: 10.1016/j.devcel.2007.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Disruption in Drosophila Apoptosis

Abstract: Mitochondrial disruption is a conserved aspect of apoptosis, seen in many species from mammals to nematodes. Despite significant conservation of other elements of the apoptotic pathway in Drosophila, a broad role for mitochondrial changes in apoptosis in flies remains unconfirmed. Here, we show that Drosophila mitochondria become permeable in response to the expression of Reaper and Hid, endogenous regulators of developmental apoptosis. Caspase activation in the absence of Reaper and Hid is not sufficient to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
183
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(205 citation statements)
references
References 43 publications
14
183
1
5
Order By: Relevance
“…This stands in stark contrast to the situation observed in the nematode and mammal, and has led to supposition that Drosophila might be an evolutionary outlier, or indeed that the mitochondrial pathway of apoptosis might not be as conserved as once thought. However, a recent study by Abdelwahid et al 54 indicates a significant, if somewhat puzzling, role for the mitochondria in programmed cell death in the fly. Abdelwahid et al found that, upon apoptosis, Reaper and HID proteins cause mitochondrial fragmentation and release of cytochrome c in both cultured S2 cells and in the developing fly embryo.…”
Section: Conservation Of a Mitochondrial Role In Cell Death: A Fly Inmentioning
confidence: 99%
“…This stands in stark contrast to the situation observed in the nematode and mammal, and has led to supposition that Drosophila might be an evolutionary outlier, or indeed that the mitochondrial pathway of apoptosis might not be as conserved as once thought. However, a recent study by Abdelwahid et al 54 indicates a significant, if somewhat puzzling, role for the mitochondria in programmed cell death in the fly. Abdelwahid et al found that, upon apoptosis, Reaper and HID proteins cause mitochondrial fragmentation and release of cytochrome c in both cultured S2 cells and in the developing fly embryo.…”
Section: Conservation Of a Mitochondrial Role In Cell Death: A Fly Inmentioning
confidence: 99%
“…Two recent studies have shown that Drp1-mediated fragmentation of the mitochondrial network during apoptosis is also conserved in Drosophila melanogaster (Abdelwahid et al 2007;Goyal et al 2007). Disruption of the mitochondrial network has been shown to occur in vivo during physiological developmental programmed cell death and when primary fly cells cultured in vitro are exposed to a variety of apoptotic stimuli, including etoposide, actinomycin D, cyclohexamide, and C 6 -ceramide (Goyal et al 2007).…”
Section: Post-translational Modification Of Drp1 Regulates Its Role Imentioning
confidence: 99%
“…The central nervous system is enlarged in Drp1 mutant flies, also indicating that developmental cell death requires the mitochondrial fission machinery (Goyal et al 2007). Expression of Hid and Reaper in fly cells has been shown to result in alterations in mitochondrial morphology and cytochrome c release (Abdelwahid et al 2007). It has been demonstrated that these changes are related to caspase activation, although not as a direct consequence since caspase activation alone does not result in these mitochondrial disruptions.…”
Section: Post-translational Modification Of Drp1 Regulates Its Role Imentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms by which Debcl and Cyt-c activate apoptosis remain unclear, these results suggest that mitochondria contribute to Drosophila apoptosis in several cellular contexts. The recent observation that mitochondrial fission is required for apoptosis, further implies that mitochondria have an important function in Drosophila apoptosis [32,33].…”
Section: The Role Of Mitochondria In Apoptosismentioning
confidence: 99%